INDEPENDENT AUDIT COMMITTEE, VOLUNTARY DISCLOSURE, INFORMATION ASYMMETRY AND VOLUME OF TRANSACTION: A MODELLING STUDY OF - Pangaribuan, Hisar; Septiani, Yuwaninda (Jurnal Ekonomis, 2018)
This study developed a model of the variables independent audit committee, voluntary disclosure, information asymmetry and volume of transaction in order to investigate the direct and indirect effect among the built variables. Data were collected from annual reports of banking companies listed on IDX. The Hypotheses testing performed with a variance-based approach using Smart- PLS in the data processing. The results of this study confirmed that an increase of the number independent audit committee members can effectively perform their overseeing function over management in order to make a better voluntary disclosure, reduced information asymmetry and increased volume of transaction. The findings of this study become more special where this research emphasizes the importance of corporate information disclosure to the public. Voluntary disclosure can significantly mediate the effect of independent audit committees on a volume of transaction, moreover, a high voluntary disclosure has a direct significant effect in reducing the level of information asymmetry so that the information asymmetry can be a mediating variable for the effect of voluntary disclosure on a volume of transaction.